2005
DOI: 10.1097/01.aog.0000146641.98665.b6
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Sexual Assault Against Women: Frequency, Health Consequences, and Treatment Outcomes

Abstract: Sexual assault is experienced by most physically abused women and associated with significantly higher levels of PTSD compared with women physically abused only. The risk of reassault is decreased if contact is made with health or justice agencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(214 citation statements)
references
References 30 publications
4
199
0
8
Order By: Relevance
“…male partners often repeatedly perpetrate sexual violence including rape and sexual coercion, [4][5][6][7][8] both of which increase abused women's risk for contracting HIV or other sexually transmitted infections if her partner is infected. There is also evidence indicating that physically abusive men engage in riskier sexual behavior than their nonviolent counterparts, including having multiple sexual partners.…”
mentioning
confidence: 99%
“…male partners often repeatedly perpetrate sexual violence including rape and sexual coercion, [4][5][6][7][8] both of which increase abused women's risk for contracting HIV or other sexually transmitted infections if her partner is infected. There is also evidence indicating that physically abusive men engage in riskier sexual behavior than their nonviolent counterparts, including having multiple sexual partners.…”
mentioning
confidence: 99%
“…Sexual assault, which is an aspect of all the aforementioned issues, has consistently yielded the highest rates of PTSD compared to any other traumatic event (Norris, 1992;McFarlane et al, 2005). Violations of sexual intimacy are extremely harmful to an individual and their development.…”
Section: Definition and Current Situationmentioning
confidence: 99%
“…In a survey of over 4,000 women undertaken in the US, the estimated pregnancy rate following rape was found to be one in twenty (5 per cent), equating to 32,101 rape-related pregnancies in one year in the US alone (Holmes et al, 1996). Within situations of intimate partner sexual violence and rape, McFarlane et al (2005) found that 20 per cent of women had a rape-related pregnancy, and 15 per cent reported contracting at least one sexually transmitted disease. The risk of HIV infection following rape is uncertain, and although generally regarded as low, local HIV prevalence and multi-perpetrator rape will affect transmission risk (WHO, 2013a).…”
Section: Health Impacts Of Rapementioning
confidence: 99%